Genetic Polymorphisms of Functional Candidate Genes and Recurrent Acute Otitis Media With or Without Tympanic Membrane Perforation. Issue 42 (October 2015) - Esposito, Susanna; Marchisio, Paola; Orenti, Annalisa; Spena, Silvia; Bianchini, Sonia; Nazzari, Erica; Rosazza, Chiara; Zampiero, Alberto; Biganzoli, Elia; Principi, Nicola
Abstract : Abstract: Evaluation of the genetic contribution to the development of recurrent acute otitis media (rAOM) remains challenging. This study aimed to evaluate the potential association between single nucleotide polymorphisms (SNPs) in selected genes and rAOM and to analyze whether genetic variations might predispose to the development of complicated recurrent cases, such as those with tympanic membrane perforation (TMP). A total of 33 candidate genes and 47 SNPs were genotyped in 200 children with rAOM (116 with a history of TMP) and in 200 healthy controls. INFγ rs 12369470CT was significantly less common in the children with rAOM than in healthy controls (odds ratio [OR] 0.5, 95% confidence interval [CI] 0.25–1, P  = 0.04). Although not significant, interleukin (IL)-1β rs 1143627G and toll-like receptor (TLR)-4 rs2737191AG were less frequently detected in the children with rAOM than in controls. The opposite was true for IL-8 rs2227306CT, which was found more frequently in the children with rAOM than in healthy controls. The IL-10 rs1800896TC SNP and the IL-1α rs6746923A and AG SNPs were significantly more and less common, respectively, among children without a history of TMP than among those who suffered from this complication (OR 2.17, 95% CI 1.09–4.41, P  = 0.02, and OR 0.42, 95% CI 0.21–0.84, P  = 0.01). This study is the first report suggesting an association between variants in genes encoding for factors of innate or adaptive immunity and the occurrence of rAOM with or without TMP, which confirms the role of genetics in conditioning susceptibility to AOM.